Anti-inflammatory Role of IL-4 in Patients with Rheumatic Mitral Valve Stenosis - Abdul-Muhaimen, Nidhal; Al-Kaabi, Zaman I. L. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: IL-4 is an antibodies inflammatory cytokine which has an important role in protecting against the inflammatory reactions in most of diseases. Here, we try to highlights the role of this cytokine in chronic Rheumatic heart disease and its correlation with the extent of histopathological abnormalities. Patients and Methods: Rheumatic mitral valve surgical fragments were taken from a total of 48 Iraqi patients with chronic rheumatic heart disease under mitral valve replacement surgery in Ibn Al- Bitar Hospital for Cardiac Surgery-Iraq-Baghdad. Paraffin embedded mitral valve tissue sections were prepared. IL-4-expressing cells were detected by using immunohistochemical staining technique and histopathological picture was studied by using hematoxylin and eosin staining. Results: There were lower numbers of IL-4 positive cells in all patients under study in general, but very lower IL-4 positive cells percentage was recorded in high risk group patients. There was no significant difference in the distribution of IL-4 mean positive cell’s count among all patients (p > 0.05). There was a correlation of IL-4 with the extent of histopathological abnormalities, and odds ratio results displayed that the histopathological abnormalities which recorded in the case group 4 times than that occurred in the control group. Conclusion: IL-4 plays an important role in regulating the inflammatory responses against the heart in chronic rheumatic heart disease.